(untitled) - Sherman, Dennis (Boston, 2004)
The West in the World relates the story of how the west has transformed and been transformed by - the rest of the world. The authors examine the Wests contributions to the world and how the west has changed and embraced new ideas through contact with the people outside its center. Using a political / cultural framework the text weaves a strong thread of social history into the narrative by showing how civilizations grow and are shaped through the decisions and actions of real people. The authors bring history to life by using art and maps as a central feature of learning. They build discussions of art into the narrative to help students interpret artwork, and provide analytical map guides that reveal the connections between geography, politics, and other developments. This strong, rich narrative is short enough to allow instructors the flexibility of introducing other sources and books as supplement, while giving students a solid understanding of Western Civilization without overwhelming them. .
Keywords: Civilization, western; History